Does Islamic value satisfaction mediate the impact of destination image, service quality, and tourist experience on revisit intention? - Sri Asmira; Muhammad Wahyuddin Abdullah; Abdul Wahid Haddade (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — The purpose of this study is to provide a description and analysis of the direct and indirect impacts of destination image, service quality, and tourist experience on revisit intention mediated by Islamic value satisfaction.Method — This research utilizes associative quantitative methods and purposive sampling techniques. The study population consists of all tourists who visited the Tongke-Tongke Mangrove Forest tourist destination. A total of 114 Muslim tourists that meet the criteria were included in the analysis. The collected data was then analyzed using Structural Equation Modeling (SEM).Result — The study found that destination image does not significantly impact Islamic value satisfaction, while service quality and tourist experience do. Destination image, service quality, tourist experience, and Islamic value satisfaction all significantly influence revisit intention. Notably, destination image does not affect revisit intention when mediated by Islamic value satisfaction, but service quality and tourist experience do.Novelty — This study focuses on sharia-based tourism research that incorporates Islamic values. Previous research has yielded inconsistent results regarding the connection between destination image, service quality, and tourist experience in relation to revisit intention. To address this, a new concept called Islamic value satisfaction is introduced, which is expected to mediate the relationship between these variables and enhance their significance.